The Implementation of Tax Payments Due to Systematic Land Registration in the DKI Jakarta Area - Muhamad Abdurahman Arasyid (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
The aim of this study is to find out what tax payment procedures need to be carried out by applicants for systematic land registration or what is also called a complete systematic land registration program (PTSL), especially in the DKI Jakarta area. This study uses normative legal research methods with statutory and comparative approaches. The results of the study show that in the implementation of Complete Systematic Land Registration which is based on Presidential Instruction Number 2 of 2018 and Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 6 of 2018, the PTSL program is in conflict with Law Number 28 of 2009 concerning Taxes Regions and Regional Levies in conjunction with DKI Jakarta Regional Regulation Number 18 of 2010 concerning Fees for Acquisition of Land and Building Rights. In implementing the PTSL Program, the provisions regarding land rights applicants being required to pay tax first before the certificate is issued are set aside, so that certificates can be issued by the Land Office without the land rights applicant needing to pay first. In this article, the author will discuss the implementation of land registration tax payments for which certificates have been issued in the PTSL Program.